2014
DOI: 10.1371/journal.pmed.1001733
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Preventive Treatment of Malaria in Pregnancy with Mefloquine in HIV-Negative Women: A Multicentre Randomized Controlled Trial

Abstract: Clara Menéndez and colleagues conducted an open-label randomized controlled trial in HIV-negative pregnant women in Benin, Gabon, Mozambique, and Tanzania to evaluate the safety and efficacy of mefloquine compared to sulfadoxine-pyrimethamine for intermittent preventative therapy for malaria. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
146
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 113 publications
(154 citation statements)
references
References 44 publications
(55 reference statements)
4
146
4
Order By: Relevance
“…Recently, a larger clinical trial conducted in five African countries confirmed that MQ at the dose of 15 mg/kg was not associated with an increased risk of severe neuropsychiatric effects. 7 Another strength of this study is the way in which missing data were handled. Missing data on LBW, placental malaria, and maternal anemia were likely to be random since most deliveries, which occurred outside the maternity clinics and for which outcomes could not be measured, were associated with traveling from outside the study area or transportation difficulties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, a larger clinical trial conducted in five African countries confirmed that MQ at the dose of 15 mg/kg was not associated with an increased risk of severe neuropsychiatric effects. 7 Another strength of this study is the way in which missing data were handled. Missing data on LBW, placental malaria, and maternal anemia were likely to be random since most deliveries, which occurred outside the maternity clinics and for which outcomes could not be measured, were associated with traveling from outside the study area or transportation difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Although concerns have been raised about a possible increase in stillbirths in women treated with curative doses of MQ, 19 this finding was confirmed neither in larger datasets nor in two recent multicenter trials on MQ for IPTp conducted in around 6,000 pregnant women. 6,7,9,20,21 As guidelines, we would recommend not including overcoming AE criteria such as stillbirths, congenital malformations, or mother-to-child transmission (MTCT) of HIV-when relevant-in the multiple outcome analysis since these outcomes have to be evaluated separately, prior to other criteria. In such cases where the drug "under test" has been associated with a significant increased risk for one of these major outcomes, we consider that the multiple outcome approach is not appropriate because the drug should not be given in this indication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from the trial showed no differences in mortality, morbidity and nutritional status between infants born to women allocated to either study group [23,24]. As part of clinical trial procedures, at delivery, newborns were given a study number to be uniquely identified.…”
Section: Study Proceduresmentioning
confidence: 99%